Highly stretchable, fast thermal response carbon nanotube composite heater. (August 2021) - Xu, Fujun; Aouraghe, Mohamed Amine; Xie, Xing; Zheng, Liangang; Zhang, Kun; Fu, Kun Kelvin
Highlights: A highly stretchable and fast response carbon nanotube heater was developed. As-prepared CNT heater can reach 206 °C with applied voltage (2 V) and in 30 s. The conductivity of the heater remains unchanged at 100 cycles repeating deformation. The CNT heater can act as a "battery starter" for batteries in low environment. Abstract: The electrical performance of delicate electro-devices is subjected to the external environment, suffering significant performance decay in conditions with extremely low temperature. In this study, a highly stretchable and high effective carbon nanotube (CNT) heater was developed for multiple applications. The CNT-based heater has good stretchability with the strain of 105%, and a high thermal response that reached 206 °C with a limited applied voltage (2 V) and heating up time (~30 s). Our results indicated that the conductivity of the heater could remain unchanged (only 0.2% variation) at 100 cycles repeating deformation. We demonstrated a potential application of using CNT heater as a "battery starter" to provide an external heating source for batteries at low temperatures. Furthermore, our work provided a universal approach to design flexible and wearable heater to offer promising opportunities for thermal management in wearable applications and electro-devices.